2010
DOI: 10.1111/j.1423-0410.2010.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Miltenberger blood group antigen subtype III (Mi.III) supports Wrb expression

Abstract: The elevated Wr(b) levels in Mi.III RBCs were likely linked to their higher band 3 levels. Higher band 3 densities on the Mi.III+ cell surface conceivably could drive complex formation between band 3 and GPA/Gp.Mur, thereby increasing the expression of Wr(b) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…1). Although the expression levels of band 3 were 25% or more in Mi.III than non-Mi.III ghosts (15,38), the expression levels of unglycosylated and glycosylated AQP1 monomers and oligomers were similar ( Fig. 1B).…”
Section: Strong Aqp1-band 3 Interaction Identified In Gpmur Erythrocmentioning
confidence: 70%
“…1). Although the expression levels of band 3 were 25% or more in Mi.III than non-Mi.III ghosts (15,38), the expression levels of unglycosylated and glycosylated AQP1 monomers and oligomers were similar ( Fig. 1B).…”
Section: Strong Aqp1-band 3 Interaction Identified In Gpmur Erythrocmentioning
confidence: 70%
“…Rh polypeptides on intact erythrocytes were immunolabelled with BRIC 69 (BITS), a monoclonal antibody targeting a region common to RhD and RhCcEe polypeptides [21–23]. Band 3 was immunolabelled with the two monoclonal anti‐band 3 antibodies – BRIC 6 and BRIC 71 – as previously described [13]. The immunolabelled erythrocytes were then stained with Alexa Fluor 488‐conjugated or 660‐conjugated anti‐mouse antibody (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that Mi.III+ RBCs often exhibit higher levels of band 3 and the Wright b (Wr b ) antigen on band 3 [12,13]. On the erythrocyte surface, band 3 interacts directly with glycophorin A (GPA), carbonic anhydrase and the Rh complex.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is no evidence of impaired P. falciparum invasion in HAG ϩ red cells, which have altered Wr b expression (557). Interestingly, Wr b is overexpressed on Mi.III red cells, an unusual hybrid glycophorin commonly encountered in Asia (559,560). The Wr a/b site in AE1 shows evidence of positive evolution in primates and other mammals (538).…”
Section: Glycophorin a And Malariamentioning
confidence: 99%